The Role of Statistical Methods in Confirming or Refuting Economic Relationships: Inflation and Unemployment Rate as a Case Study (Czech Journal of Multidisciplinary Innovations, 2025)
This study aims to examine the relationship between the inflation and unemployment rates in Iraq during the period from 2004 to 2022, using a set of modern statistical and economic methods, including the stationarity test (Phillips–Perron), linear regression analysis, Granger causality test, and cointegration test (Johansen–Juselius). The research seeks to clarify the nature of the relationship between these two important economic variables, both in the short and long term, to determine whether this relationship aligns with what traditional economic theory and the Phillips curve suggest—namely, an inverse relationship between inflation and unemployment—or whether it differs under the specific conditions of the Iraqi economy.